1967
DOI: 10.1103/physrev.163.843
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of Phonons by Monatomic Impurities in Potassium Halides

Abstract: VII. CONCLUSIONSThe optical constants of potassium bromide (VT, 8I, pi, k M , €EO, an d X T) vary linearly with temperature within the experimental accuracy. Lorentz theory permits us to consider two linear oscillators, which represent quite well the behavior of KBr, if they are modified to include a temperature dependence. The damping of the fundamental oscillator decreases when T decreases. On the other hand, its strength does not vary much, while the strength of the second oscillator decreases strongly. ACK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1969
1969
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…This also explains earlier success of the approach, in which foreign impurities in dielectric crystals were regarded as pure isotopic admixtures, e.g., Ref. 4. Concluding, the thermal conductivity of pure and carbon-monoxide-doped nitrogen crystals has been measured for the samples containing 0.2, 0.25, 0.3, 0.5 and 0.7% of CO molecules, in the temperature range 1.2-26 K. The simple analysis has shown that the scattering of phonons on admixture molecules possessing the same mass as the host molecule is relatively weak when compared with the scattering on a molecule featuring different mass.…”
Section: Resultsmentioning
confidence: 82%
“…This also explains earlier success of the approach, in which foreign impurities in dielectric crystals were regarded as pure isotopic admixtures, e.g., Ref. 4. Concluding, the thermal conductivity of pure and carbon-monoxide-doped nitrogen crystals has been measured for the samples containing 0.2, 0.25, 0.3, 0.5 and 0.7% of CO molecules, in the temperature range 1.2-26 K. The simple analysis has shown that the scattering of phonons on admixture molecules possessing the same mass as the host molecule is relatively weak when compared with the scattering on a molecule featuring different mass.…”
Section: Resultsmentioning
confidence: 82%
“…A concentration of 1·0 % Y in CaF 2 was necessary to produce an anomalous thermal conductivity dip, while Baumann and Pohl (1967) found dips for ,....,0·02% TI in KCI. The purpose of the present paper is to analyse the thermal conductivity of the doped CaF 2 in order to suggest a reason for such differences.…”
Section: Previous Workmentioning
confidence: 99%
“…Only the latter is discussed here in detail, and for details of the others the reader is referred to Klemens (1955), Berman and Brock (1965) and Klein (1966). Baumann and Pohl (1967) have discussed the relative difficulty found in fitting experimental data by resonant scatter relaxation rates. Many forms have been used which are theoretically justifiable (Schwartz and Walker 1967).…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations